Sex Determination by Discriminant Function Analysis from Femoral Histomorphometry of a Nigerian Population - Clinton David Orupabo; Loveday Ese Oghenemavwe (Archives of Current Research International, 2024)
Aim: Thorough analysis of skeletal bones has progressed with time from superficial observations to histomorphometry. This is to enable more accurate and precise information to help in the identification of victims. This study intends to develop a model for sex estimation from histomorphometric parameters using discriminant function analysis (DFA). Study Design: This is a cross-sectional study design. Place of Study: Skeletal collections from the Anatomy and Pathology Departments of University of Port Harcourt, Nigeria between May 2021 and March 2023. Methodology: The midshaft of the right femur of 105 individuals (78 males and 27 females), within the age range of 21 and 60 years was utilized for this study. Skeletal remains were obtained from cadaveric specimens from the Anatomy Department of University of Port Harcourt. Ground sections of the bone specimen were done using Modified Frost’s manual method of bone preparation. Results: The data were analyzed using SPSS version 23 and an Image J software was utilized to quantify and measure the histomorphometric properties. The results show secondary osteons (OSS) to be higher in the males while fragmented osteons (OSF) were higher in the females. The femur bone shows fitness for DFA at a canonical correlation of 0.631. Also, a cross validation shows that 82% of the cases are correctly classified as males and 81.5% as females. A sex estimation model was therefore developed with any discriminant score equals or close to – 0.520 indicates males and scores equals or close to 1.253 indicating female. Conclusion: The findings can therefore be utilized to determine sex of Nigerians using a sex model as established by this study, which could help forensic case diagnosis.